A comparative study of text steganography and linguistic steganography - Utama, Sunariya; Din, Roshidi; Mahmuddin, Massudi (2015)
This papers present classification steganography method on text domain based on the perspective of researchers effort in last decade, it has been analyzed the categories of method steganography in medium of text; text steganography and linguistic steganography.